Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Kaki Lima (Studi Di Seputar Alun-Alun Kabupaten Klaten) - Handika, Anang, Siti Fatimah NH, SE, M.si (2017)
This study entitled "Analysis of Factors Affecting income street vendors around the square in Klaten district in 2017". This study aimed to analyze and determine how much influence the initial capital, lam business, number of employees, hours and levels of education to income street vendors around the square in Klaten district. The population of as many as 110 vendors. The samples with judgment sampling method with a total sample of 29 respondents consisting of 22 respondents traders of food and drinks, one person draper, 4 traders accessories and 2 merchants obtan cigarettes or drugs. In this study using multiple linear regression analysis model of ordinary least squares (OLS). The results of the analysis are: (1) The calculation data normality test with Bera Jurque normal distribution models; (2) Results of linearity test with Ramsey models Research shows that the model be linear; (3) The test results showed the classical assumption that there are no issues multicoloniarity and heteroskedatisitas, autocorrelation problems occur; (4) The results of t-test showed that the variables of initial capital, number of employees and the level of education and significant effect sedagkan old variable opening hours of effort and no significant effect; (5) F test results indicate the model used to exist; (6) R2 scored 55.14% which means that 55.14% of variation income street vendors can be explained by the initial capital, the old business, number of employees, hours and levels of education. While the remaining 44.86% is explained by other independent variables were included in the model.